2018
DOI: 10.1007/s11769-018-0991-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Risk Assessment of Heavy Metals in Paddy Soils of Yongshuyu Irrigation Area from Songhua River Basin, Northeast China

Abstract: There is an increasing concern for potentially hazardous metals pollution, which can threaten crops production and human health. In this study, the spatial distribution and environmental risks of eight heavy metals in surface soil samples collected from the paddy fields in Yongshuyu irrigation area, Northeast China were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…PC1, consisting of Pb, Ni, and Cr, comes from the same natural source, such as lithogenic components controlled by parent materials. is finding is also confirmed in previous studies that report low Pb, Ni, and Cr contaminations from natural sources [20,37,38]. Based on the correlation coefficient and PCA results, Cd and Co in the second component (PC2) are not intercorrelated.…”
Section: Principal Component Analysis (Pca) Resultssupporting
confidence: 89%
“…PC1, consisting of Pb, Ni, and Cr, comes from the same natural source, such as lithogenic components controlled by parent materials. is finding is also confirmed in previous studies that report low Pb, Ni, and Cr contaminations from natural sources [20,37,38]. Based on the correlation coefficient and PCA results, Cd and Co in the second component (PC2) are not intercorrelated.…”
Section: Principal Component Analysis (Pca) Resultssupporting
confidence: 89%
“…Therefore, soil profile was studied from 0 to 100 cm at the four sampling sites of smelter in this study. The results indicated that total Cd content of all sampling soils exceeded secondary standard maximum allowable value of environmental quality standard for soil (GB15618-1995) (Cui et al, 2018). On the contrary, total Cr content did not exceed by the concentration limit.…”
Section: Discussionmentioning
confidence: 78%
“…PC2 was predominated by Pb, Hg, Cd, and Zn. The soil Pb and Hg may be correlated to the developed transportation industry in the PRD, which is an important automobile exhaust and production center [41][42][43]. A certain amount of soil Pb and Cd may be the result of waste gas emissions from vehicles, as well as the combustion of Pb-containing gasoline [4].…”
Section: Source Apportionment By Pca-mlr Modelmentioning
confidence: 99%